Comparison of gut microbiota in male MAFLD patients with varying liver stiffness - Zhang, Yuheng; Yan, Su; Sheng, Shifeng; Qin, Qian; Chen, Jingfeng; Li, Weikang; Li, Tiantian; Gao, Xinxin; Wang, Lin; Ang, Li; Ding, Suying (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose In this study, we examined the changes to the composition and function of the gut microbiota from patients with metabolic dysfunction-associated fatty liver disease (MAFLD).We compared patients in a case group (liver stiffness (LSM) ≥ 7.4 kPa) with a matched control group (LSM < 7.4 kPa) and investigated the correlation between characteristics of the microbiota and other biochemical indicators. Methods The study looked at a total of 85 men with MAFLD, 17 of whom were in the case group and 68 of whom were in the control group. We measured waist circumference, blood pressure, and body mass index, as well as clinical parameters including liver stiffness, enzyme levels, cholesterol levels, and fat attenuation. Whole-genome shotgun sequencing technology and the MetaCyc database were then used to detect the composition and major pathways of the gut microbiota for each patient. Statistical analyses were performed, including the chi-square test, the student’s t-test, the Wilcoxon rank-sum test, and the Mann–Whitney test. Results Whole-genome sequencing showed that the composition of the gut microbiota in patients with an LSM of above 7.4 kPa was significantly different to that of the control group. There were seven bacterial species that were different between the two groups. Prevotella copri, Phascolarctobacterium succinatutens, Eubacterium biforme, and Collinsella aerofaciens were enriched in the case group (P < 0.05). Conversely, Bacteroides coprocola, Bacteroides stercoris and Clostridiales bacterium 1_7_47FAA were decreased in the case group (P < 0.05). Furthermore, after removing low abundance pathways, a total of 32 microbial pathways were found to be significantly different between the two groups. Most pathways enriched in the case group over the control were related to biosynthesis of metabolites including amino acids, vitamins, nucleosides, and nucleotides. Conclusion. The composition and function of the gut microbiota in patients with increased liver stiffness are significantly altered. This observation may provide new avenues to better understand the mechanism of liver fibrosis.